Manajemen Krisis PR Es Teh Indonesia dalam Pemulihan Image Negatif Pasca Somasi Konsumen pada Akun Twitter @gandhoyy - Muhammad Fadeli, S.Sos.M.Si; Dr. Fitria Widiyani Roosinda, S.Sos, M.Si; Cindy Meidina Trihapsari (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2023)
The purpose of this research is to find out the crisis management of Indonesian Ice Tea PR in the recovery of the negative image after consumer subpoenas on the Twitter account @gandhoyy in three phases, namely pre-crisis, crisis-response, and post-crisis. This study uses a qualitative descriptive method with the object of PR Es Teh Indonesia and the Twitter account @gandhoyy. Data was taken by observation, interview, and documentation techniques. The interview was conducted with the Head of Public Relations of PT. Es Teh Indonesia via company email. The results showed that during the pre-crisis phase, PR representatives from PT. Es Teh Indonesia identified the problem by discussing tweets from the Twitter account @gandhoyy with related parties. Then the organization gives a subpoena for defamation. Instead of taking legal action, PT. Es Teh Indonesia only wants the account owner named Gandhi to admit his guilt because the criticisms conveyed are insulting and not actual facts. Then, in the post-crisis phase, PT. Es Teh Indonesia withdrew the subpoena given to Gandhi's brother because he had already apologized. The Indonesian Ice Tea party has also made improvements by conducting an evaluation in the form of product differentiation, namely by providing a choice of sweetness level or variant of sweetness starting from no sugar (0%), slight (30%), half (50%), less (80%), and normal (100%) so that it can be adjusted to consumer tastes.